Kedudukan Perjanjian Kawin yang Dibuat Dihadapan Notaris Setelah Perkawinan - Herizky Rahmandani, Muhammad (Universitas Ekasakti, 2024)
A Marriage Agreement is an agreement between a husband and wife regarding matters that will arise in marriage. A marriage agreement is usually made by the prospective husband and wife regarding aspects of the marriage and all matters that may arise during the marriage before the marriage takes place or when the marriage takes place. However, with the issuance of Constitutional Court decision no. 69/PUU XIII/2015 determines that a marriage agreement can be made before, during and during the marriage. This article wants to discuss marriage agreements after the Constitutional Court decision above comes into effect and the position of Marriage Agreements made before a Notary after the Constitutional Court Decision comes into force. The method used is a normative juridical approach and descriptive analytical research specifications. Qualitative juridical data analysis. Constitutional Court Decision Number 69/PUU-XIII/2015 determines that marriage agreements can be made before, during and during the marriage, and there are several formats of model marriage agreements which can be a guide for notaries who will make marriage agreement deeds and agreement deeds. Marriages made before a Notary after the enactment of Constitutional Court Decision Number 69/PUU-XIII/2015 are still valid and are authentic deeds and are valid evidence.